ООО «ТЮМЕНТРАНСГАЗ»: внедрение ЛИС «ХИМИК-АНАЛИТИК»; Газовая промышленность; № 2 - Терещенко А. Г. Александр Георгиевич; Баянова Т. В.; Юшкеева Н. В.; Смышляева Е. А.; Обухова В. А.; Хорошавина Е. А. (2007, 2007)
Заглавие с титульного листа